Tvåspråkighet och Livsbanor : En undersökning av avgångselever från Gränsskolan i Haparanda - Ockenström Norberg, Emelie (Södertörns högskola, Institutionen för livsvetenskaper, 2008)
This essay deals about bilingualism and lifepaths. The essay is based on a qualitative study, where eight individuales have been interviewed, all of them from Gränsskolan in Haparanda. Before the interview´s a study of relevant research literature was made. The main purpose with the essay, is to study if the informant’s life paths have been affected by their bilingualism, i.e. if the informers moves and education etc. have been affected by theirs bilingualism. The essay also deals with how the informants’ bilingualism have developed and if there is something who has promote to the bilingualism. A plotting program called Geotime has been used to analyse the informers’ life paths. The program was used for time-geographic illustrations. The systematic and the integrative approach is the starting point in the essay´s geographic problem. Time geography is used for analysing the informers life paths. The other theory, the boundary theory is used for to examine how the informers in Haparanda had become bilingual (systematic approach). In order to understand, study and see how the life paths and bilingualism is spatially related to each other in specific environments, an investigation was made to see if there were connection between those, i.e. if moves, jobs and education had been influenced by the informers’ bilingualism (integrative approach). The study shows that the informers had been bilingual for different reasons, their knowledge in Finnish and in Swedish is different. The informers’ life paths look different, four of the informers had a wide pattern of movement. The conclusions are that the informers’ life has in certain ways been influenced by their bilingualism, because some of the informers has had use of both languages, for example at their workplaces. Denna uppsats handlar om tvåspråkighet och livsbanor. Undersökningen bygger på en kvalitativ studie, där åtta individer har intervjuats, samtliga har gått på Gränsskolan i Haparanda. Innan intervjuerna genomfördes gjordes en litteraturundersökning. Syftet ...